The Effect of Sensory Perception Stimulation Group Activity Therapy on the Ability to Control Hallucinations: A Literature Review: Pengaruh Terapi Aktivitas Kelompok Stimulasi Persepsi Sensori Terhadap Kemampuan Mengontrol Halusinasi: A Literature Review - Wijoyo, Eriyono Budi; Khotimah, Nurul; Nuraini, Nuraini (Jurnal Kesehatan Masa Depan, 2022)
ABSTRACT Background: Hallucinations are loss of self-control where in this situation the patient can commit violence including suicide, killing other people and even damaging the environment. Efforts to overcome hallucinations are done by doing a modality therapy in the form of perception stimulation group activity therapy. Research purposes: This is to analyze the effect of perceptual stimulation group activity therapy on the ability to control hallucinations Search method: literature review using a databases (Google Schoolar and Garuda). By identifying journals, screened then assessed based on full text and according to the inclusion criteria. Results and analysis: Researchers found 9 articles that met the inclusion criteria. Perceptual stimulation group activity therapy of the ability to control hallucinations is mostly quasy experiment, pre-experiment and pre-experiment. Conclusion: So it can be concluded that perceptual stimulation group activity therapy on the ability to control hallucinations is very important to do to improve the ability to control hallucinations Keywords: group activity therapy, perceptual stimulation, controlling hallucinations